School Absenteeism due to Toothache among Secondary School Students Aged 16–18 Years in the Ha'il Region of Saudi Arabia. (18th February 2016) - Shaikh, Sameer; Siddiqui, Ammar Ahmed; Aljanakh, Mohammad
Abstract : Objective . This study assessed the impact of toothache on school attendance among secondary school students in the Ha'il Region, Saudi Arabia. Methods . A cross-sectional, paper based survey was conducted among 16–18-year-old students of public sector secondary schools in the Ha'il Region, Saudi Arabia. Results . Of the 510 students selected from the participating schools, 480 were analyzed (94.1%). Of the sample, 50.4% were boys. Among the participants in the study, 86 students reported school absence due to toothache in the six months prior to the survey. Consequently, the prevalence of absenteeism due to toothache in this study was of 18%. Conclusion . The prevalence of school absenteeism due to toothache among students in the Ha'il Region was low. Yet, still, missed school days due to toothache may have implications for students also in the Ha'il Region, Saudi Arabia, as school absenteeism leads to missed opportunities for learning and academic advancement.